(untitled) (Research, Society and Development, 2021)
This article aimed to verify the existence of mobile applications that seek to assist children with microcephaly and their caregivers in health management and education. This research has an exploratory, quantitative and qualitative, bibliographic nature, carried out in the form of scientific and technological prospecting in databases of patent applications and software registers, scientific databases and virtual stores of applications. Through the searches, only 1 article was selected for analysis; it is a mobile health app aimed at caregivers of children that has Skzv as an informative tool to help track the development of these children. Are arranged in the application functions to monitor the development of the child, monitoring of visual and motor skills, registration of appointments and function that enables communication between caregivers and professionals. The application proved to be very promising in bringing information to this niche of people who need it, in addition to proving that a rapid diagnosis and adequate treatment are key points for the quality of life of children. Through this prospecting study, it is possible to state that there are several applications aimed at child care and development, but the shortage of applications aimed at managing the health of children with microcephaly is clear. Considering the high number of children with microcephaly in Brazil, it is explicit the need for health tools that can help this population.